Essentials of behavioral research : - Rosenthal, Robert (McGraw-Hill, 2008)
This classic advanced undergraduate/graduate text in research methods requires statistics as a prerequisite. The first half of the text concentrates on research methods and the second half introduces students to advanced statistical procedures